STATE, SOCIABILITY AND SOCIAL CONTROL IN COSTA RICA (1950-1971) - Urbina Gaitán, Chester (2006)
Among 1950-1971 the costa rican State structured its control and direction of thesociability mainly on the public spectacles and the sports activity, being emphasizedin this last one the soccer.